2001
DOI: 10.1046/j.1460-2695.2001.00383.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue crack growth and crack closure in an AlMgSi alloy

Abstract: This study reports an experimental investigation of fatigue crack propagation in AlMgSi1‐T6 aluminium alloy using both constant and variable load amplitudes. Crack closure was monitored in all tests by the compliance technique using a pin microgauge. For the constant amplitude tests four different stress ratios were analysed. The crack closure parameter U was calculated and related with ΔK and the stress ratio, R. The threshold of the stress intensity factor range, ΔKth , was also obtained. Fatigue crack propa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
59
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 28 publications
13
59
0
3
Order By: Relevance
“…As reported for single overloads in the analysed alloy [6,7] the observed crack growth trends under periodic overloads are consistent with the plasticity-induced crack closure phenomenon. Each overload produces higher monotonic plastic zone than the baseline loading.…”
Section: Crack Closuresupporting
confidence: 72%
See 2 more Smart Citations
“…As reported for single overloads in the analysed alloy [6,7] the observed crack growth trends under periodic overloads are consistent with the plasticity-induced crack closure phenomenon. Each overload produces higher monotonic plastic zone than the baseline loading.…”
Section: Crack Closuresupporting
confidence: 72%
“…In recent work, the authors observed that the plasticity-induced crack closure phenomenon could generally explain the crack growth behaviour following single peak overloads under both load control mode [6] and constant DK conditions [7]. The present work intends to analyse the fatigue crack growth due to several loading sequences containing periodic single overloads and to clarify if the observed behaviour can also be correlated with the crack closure phenomenon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This discrepancy was justified by Paris et al [24], who suggested the "partial closure model". Borrego et al [25] concluded that crack closure explained the bias of stress ratio on the fatigue crack growth rate for the 6082-T6 aluminum alloy and the influence of several load parameters for overloads interactions if the partial crack closure model is included in the analyses.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental crack shapes were obtained by Borrego in crack closure studies [21] made in MT specimens according to the standard ASTM E647. Specimens with a fixed thickness of 3 mm were considered (the other dimensions are similar to the ones indicated in Fig.…”
Section: Experimental Validationmentioning
confidence: 99%